On-field prediction vs monitoring of aerobic capacity markers using submaximal lactate and heart rate measures - Garcia-Tabar, I.; Izquierdo, M.; Gorostiaga, E. M. (Scandinavian Journal of Medicine & Science in Sports, 2017)
This study aimed to validate the use of a single blood lactate concentration measurement taken following a 5-minute running bout at 10 km·h-1 (BLC10) and the speed associated with 90% of maximal heart rate (S90) to predict and monitor fixed blood lactate concentration (FBLC) thresholds in athletes. Three complementary studies were undertaken. Study I: A cross-sectional study examining the associations of BLC10 and S90 with running speeds at FBLC of 3 (S3mM) and 4 mmol·L-1 (S4mM) in 100 athletes. Study II: A cross-validation study assessing the predictive capacity of BLC10 and S90 to estimate FBLC thresholds in real practice. Study III: A longitudinal study examining whether training-induced changes in FBLC thresholds could be monitored using BLC10 and S90 in 80 athletes tested before and after an intensified training period. Study I: BLC10 (r=-.87 to -.89) and S90 (r=.73-.79) were very largely (P<.001) related to FBLC thresholds. Study II: Predictive models yielded robust correlations between estimated and measured FBLC thresholds (r=.75-.91; P<.001). The limits of agreements, however, revealed that prediction of FBLC thresholds could be biased up to 9%-15%. Study III: BLC10 was very largely related to training-induced changes in FBLC thresholds (r=-.72 to -.76; P<.001). Increases in S90 were associated with improvements in FBLC thresholds, but decreases in S90 led to unclear changes in FBLC thresholds. This study supports the use of BLC10 as a simple, low-cost, non-fatiguing, and time-efficient functional variable to monitor, but not predict, FBLC thresholds in athletes. The present results also question the use of S90 to detect declines in endurance performance.